Hydrogeochemical origin and circulation of spring waters along the Karakorum fault, Western Tibetan Plateau: Implications for interaction between hydrosphere and lithosphere - Wang, Jingli; Zhou, Xiaocheng; He, Miao; Li, Jingchao; Dong, Jinyuan; Tian, Jiao; Yan, Yucong; Li, Ying; Liu, Kaiyi; Li, Yang (Frontiers in Earth Science, 2022)
Geochemical investigation on the origin and circulation of geothermal water is crucial for better understanding the interaction between hydrosphere and lithosphere. Previous studies on the Himalayan geothermal belt mainly distributed in the central and eastern Tibetan Plateau. In this study, water samples (8 hot springs and 1 cold spring) from the Karakorum fault (KKF) zone of western Tibetan Plateau were analyzed for the hydrogeochemical characteristics and isotopic compositions. Three types of spring water along the KKF were classified on basis of ionic concentration and Sr isotopic composition: type A water (HCO3–Mg or Ca), type B water (HCO3–Na) and type C water (Cl–Na). Type A water is originated from the infiltration of meteoric water and the dissolution of silicate/evaporite. Type B water is mainly leached from the metamorphic and granitoid rocks. Type C water is formed by the dissolution of chlorides and sulphates. δD and δ18O isotopes indicate that geothermal fluid along the fault zone was mainly recharged by local precipitation. Moreover, reservoir temperatures of 144.2–208.6 °C were estimated by the silica–enthalpy mixing model, and the thermal waters have a relatively deep circulation depth (≥ 7.0 km). Meanwhile, the thermal waters are characterized by extremely high Li, B, Fe and As concentrations and earthquakes frequently happened in the vicinity, suggesting that the KKF is a deep and active fault, which also indicates that the thermal fluids are strongly associated with seismicity. Therefore, thermal fluid can potentially be used as continuous monitoring sites for earthquake forecasting.